THE USE OF MODERN COMBINED ADDITIVE AGENTS FOR DIRECTLY COMPRESSED ORODISPERSIBLE TABLETS - Z. M. Kozlova; S. O. Pchelintcev; E. R. Khalikova; P. G. Zabolotnaya; M. N. Maslova; G. A. Kim (Разработка и регистрация лекарственных средств)
The article describes the comparison results of the compression mass technological characteristics and quality profile of dosage forms produced with the use of modern combined additive agents. Technological parameters such as the flowability and bulk density of the compositions were analyzed. Orodispersible tablets were produced by direct compression. The quality of the tablet compositions was investigated in terms of appearance, average tablet weight, friability, hardness and disintegration.